The teaching-learning of colors and shapes in early childhood education: an experience with students with Autistic Spectrum Disorder (ASD) (Research, Society and Development, 2020)
The discussion on school inclusion of students who have specific needs is increasingly present in society. It is necessary to provide adequate means and conditions for the learning of these students and include them with others, such as: differentiated classes, games and educational games that facilitate learning. Actions like these and others allow their development. Therefore, the present study proposed to report the contributions to the inclusion based on an activity “Buying my favorite fruit” developed with a student with Autism Spectrum Disorder (ASD) in a class of Early Childhood Education. A dynamic activity of visiting a food trade was applied, where students bought a fruit of their preference, on site it was explained about the shapes, varieties and colors of fruits, vegetables and legumes. Soon after, students returned to school to be explained about the use of fruits and waste generated after consumption, such as peel and seeds. The tasting of these fruits was then carried out, and after this stage the students performed an activity in the book regarding the practice. During the activity, it was observed, the participation of the student with ASD. The attitudes of the teacher were opposite to the usual in the classroom, the aggressiveness, the constant agitation and the difficulty of concentration gave way to the interest and accomplishment of the activity, besides the greater affection and involvement with colleagues and teachers. Therefore, differentiated pedagogical strategies expand learning possibilities and, as well as, the function of effectively serving students with specific needs.